Psychiatrists’ Understanding and Management of Conversion Disorder: A Bi-National Survey and Comparison with Neurologists - Dent B (Dove Medical Press, 2020)
Benjamin Dent,1 Biba R Stanton,2– 4 Richard A Kanaan1,4 1Department of Psychiatry, University of Melbourne, Austin Health, Heidelberg, VIC, Australia; 2Department of Neurology, King’s College Hospital, London, UK; 3Department of Neuropsychiatry, South London & Maudsley NHS Trust, London, UK; 4Institute of Psychiatry, Psychology and Neurosciences, King’s College London, London, UKCorrespondence: Richard A Kanaan Department of PsychiatryAustin Health, LTB10, 145 Studley Road, Heidelberg, VIC 3084, AustraliaTel +61394963351Fax +61394590821Email richard.kanaan@unimelb.edu.auBackground: A 2011 survey of neurologists’ attitudes to conversion disorder found a tacit acceptance of the psychological model but significant ambivalence around its relationship to feigning. These issues are under increased scrutiny as the DSM-5 revision removed both the requirement for a psychological formulation and the exclusion of feigning from the diagnostic criteria. Whether those attitudes are shared with psychiatrists is unknown.Methods: An online survey of the Section of Neuropsychiatry, Royal Australian and New Zealand College of Psychiatrists, and the Faculty of Neuropsychiatry, Royal College of Psychiatrists (UK), on their understanding and management of conversion disorder in February 2019. Statistical comparisons are made with our previous survey of Neurologists.Results: A total of 52 Australian and 131 UK-based members completed the survey which revealed similarities but also clear differences from their neurological colleagues. The psychiatrists strongly endorsed a psychogenic model for conversion disorder, and the conversion model in particular, though many models were employed. They felt a psychiatric assessment was essential to the diagnosis of conversion disorder, and they often disagreed with the diagnosis in neurology referrals of putative conversion disorder. Most felt that a psychiatric formulation was supportive, and many that it was necessary to the diagnosis. They saw feigning as usually present to a degree but were more comfortable with discussing this than neurologists.Conclusion: Psychiatrists use psychosocial models for conversion disorder and see an overlap with feigning. They believe psychiatrists are essential for the diagnostic process and would not usually support a diagnosis without a psychiatric formulation.Keywords: conversion disorder, functional neurological disorder, neuropsychiatrist, attitudes, feigning